2018
DOI: 10.1002/fee.1974
|View full text |Cite
|
Sign up to set email alerts
|

Responding to climate change in forest management: two decades of recommendations

Abstract: Recommendations for responding to climate change in forest management have proliferated over the past two decades. A systematic review of the scientific literature revealed that the majority of such recommendations (86%) focused primarily on maintaining existing ecological patterns and processes via either passive or active adaptation approaches, while 14% focused on transformation to new system configurations through active interventions. Most recommendations (69%) were general, non‐specific principles and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 49 publications
0
26
0
Order By: Relevance
“…Since the Social FOI was positively associated with diverse management strategies, it is worth pointing out that the owners' networks seem to facilitate different management objectives, despite the emphasis on production in the Swedish forestry context. Active or passive forest management approaches may be advocated depending on, for example, the purpose of the management, such as maximizing certain forest functions or multifunctionality (e.g., Hagerman and Pilai 2018;Cruz-Alonso et al 2019;White and Long 2019;Williams and Powers 2019). Whereas this study showed that certain structural characteristics were associated with management inactivity (owning a smaller forest holding, being female, and owning forest in the north and middle regions in Sweden) (cf.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Since the Social FOI was positively associated with diverse management strategies, it is worth pointing out that the owners' networks seem to facilitate different management objectives, despite the emphasis on production in the Swedish forestry context. Active or passive forest management approaches may be advocated depending on, for example, the purpose of the management, such as maximizing certain forest functions or multifunctionality (e.g., Hagerman and Pilai 2018;Cruz-Alonso et al 2019;White and Long 2019;Williams and Powers 2019). Whereas this study showed that certain structural characteristics were associated with management inactivity (owning a smaller forest holding, being female, and owning forest in the north and middle regions in Sweden) (cf.…”
Section: Discussionmentioning
confidence: 74%
“…A less proactive approach to the risk of future damages in forests has been found among less engaged owners (Gan et al 2015 ). However, not implementing certain management measures may also reflect a willingness to rely on the forest’s own ability to adapt through evolutionary processes (i.e., passive adaptation) (Keskitalo et al 2016 ; Hagerman and Pilai 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It limits the analytical potential, real-world applicability and replicability of the typologies 26 , 44 , ultimately preventing cross-comparison between adaptation projects, studies, regions, and ecosystems. Furthermore, many existing reviews of adaptation actions have limited scope, for instance, by focusing only on forests 19 , 36 or terrestrial systems 43 .…”
Section: Typologies Of Adaptationmentioning
confidence: 99%
“…Recently, concepts of how to adapt forest management have been described [3][4][5]. One of the most important measures is to modify the species composition of forest stands by increasing the share of species with a high adaptation potential [3].…”
Section: Introductionmentioning
confidence: 99%